2022
DOI: 10.3389/fgene.2022.1025568
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heteroscedasticity on the prediction efficiency of genome-wide polygenic score for body mass index

Abstract: Globally, more than 1.9 billion adults are overweight. Thus, obesity is a serious public health issue. Moreover, obesity is a major risk factor for diabetes mellitus, coronary heart disease, and cardiovascular disease. Recently, GWAS examining obesity and body mass index (BMI) have increasingly unveiled many aspects of the genetic architecture of obesity and BMI. Information on genome-wide genetic variants has been used to estimate the genome-wide polygenic score (GPS) for a personalized prediction of obesity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Recently, PRS-based prediction models were constructed and assessed for various traits ( Khera et al, 2018 ; Khera et al, 2019 ; Tanigawa et al, 2022 ). However, few studies have examined heteroscedasticity of the PRS model ( Sulc et al, 2020 ; Baek et al, 2022 ). This study developed a PRS-based prediction model for 15 quantitative traits and investigated whether heteroscedasticity commonly exists in the PRS model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PRS-based prediction models were constructed and assessed for various traits ( Khera et al, 2018 ; Khera et al, 2019 ; Tanigawa et al, 2022 ). However, few studies have examined heteroscedasticity of the PRS model ( Sulc et al, 2020 ; Baek et al, 2022 ). This study developed a PRS-based prediction model for 15 quantitative traits and investigated whether heteroscedasticity commonly exists in the PRS model.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive performance for previous PRS models was evaluated without considering whether they are homoscedastic or heteroscedastic (Vilhjalmsson et al, 2015;Khera et al, 2019;Prive et al, 2020;Ruan et al, 2022;Tanigawa et al, 2022). Other studies suggest that PRS models show heteroscedasticity for obesityrelated traits (Sulc et al, 2020;Baek et al, 2022). Therefore, PRS models for other traits may also show heteroscedasticity, and it is necessary to test heteroscedasticity in PRS models for various traits.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm LDpred2 is a Bayesian method that derives genetic risk scores from genome-wide association study (GWAS) summary statistics and a linkage disequilibrium (LD) reference matrix [53,59,60]. We used the same datasets and summary statistics as for clumping and thresholding.…”
Section: Ldpred2mentioning
confidence: 99%
“…The heteroscedastic test is used to determine whether or not there are variance deviations from the residuals for all observations in the regression model [16]. Based on the results of the analysis, it was found that all variables declared independent did not experience symptoms of heteroscedasticity.…”
Section: Heteroscedasticity Testmentioning
confidence: 99%